2019
DOI: 10.18773/austprescr.2019.006
|View full text |Cite|
|
Sign up to set email alerts
|

The hot patient: acute drug-induced hyperthermia

Abstract: Drugs can cause dysregulation of the hypothalamic-pituitary-adrenal axis which can result in a rise in core temperature. This type of hyperthermia is unresponsive to antipyretics and can be complicated by rhabdomyolysis, multi-organ failure and disseminated intravascular coagulation. Organic causes of fever such as infection must be ruled out. Syndromes associated with druginduced fever include neuroleptic malignant syndrome and anticholinergic, sympathomimetic and serotonin toxicity. The class of offending dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
(16 reference statements)
0
12
0
1
Order By: Relevance
“…A wide variety of xenobiotics can affect the thermal homeostasis, triggering or exacerbating the hyperthermia-induced damage, both by the increased metabolic heat production (e.g., sympathomimetic agents) or by an impairment of heat-dissipating effector mechanisms (e.g., anticholinergic agents) [3]. This disruption will consequently affect many other homeostatic systems and may result in several life-threatening complications such as disseminated intravascular coagulation, hyperkalemia, metabolic acidosis, multi-organ failure, and rhabdomyolysis [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of xenobiotics can affect the thermal homeostasis, triggering or exacerbating the hyperthermia-induced damage, both by the increased metabolic heat production (e.g., sympathomimetic agents) or by an impairment of heat-dissipating effector mechanisms (e.g., anticholinergic agents) [3]. This disruption will consequently affect many other homeostatic systems and may result in several life-threatening complications such as disseminated intravascular coagulation, hyperkalemia, metabolic acidosis, multi-organ failure, and rhabdomyolysis [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic hypothermia improves survival and neurodevelopmental outcomes in neonates with moderate to severe hypoxic ischaemic encephalopathy [11]. In adults, two phase-two trials comparing therapeutic hypothermia at 32-34 °C with a permissive approach to temperature management suggested that therapeutic hypothermia increased survival and improved neurological outcomes following out-of-hospital cardiac arrest [12, *Correspondence: paul.young@ccdhb.org.nz 1 Intensive Care Unit, Wellington Regional Hospital, Wellington, New Zealand Full author information is available at the end of the article 13]. A subsequent trial comparing two hypothermia regimens (33 and 36 °C) showed that these resulted in similar outcomes [14].…”
Section: Temperature Management In Patients With Hypoxic Brain Injuriesmentioning
confidence: 99%
“…]. As peripheral thermometry can substantially underestimate core body temperature [20] and temperature can rise rapidly [1], it is prudent to monitor core body temperature continuously in critically ill patients with fever. Although uncommon, there are certainly instances where patients develop extremely high body temperature (> 42 °C) and die soon after [6].…”
Section: Temperature Management In Patients With Traumatic Brain Injumentioning
confidence: 99%
See 2 more Smart Citations